On Periodic Locally Solvable Groups Decomposable into the Product of Two Locally Nilpotent Subgroups - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish new results concerning various properties of a periodic locally solvable group G = A B with locally nilpotent subgroups A and B one of which is hyper-Abelian.